Pharmacists and COVID-19 - Ali Elbeddini; Thulasika Prabaharan; Sarah Almasalkhi; Cindy Tran (Taylor & Francis Group, 2020)
In the fight against COVID-19, frontline health workers have been vital to keeping the pandemic at bay, but recognition of individual professions' efforts have been inconsistent at all levels. Pharmacists around the world have continued to provide direct patient care and perform frontline duties for their communities during this pandemic, but are often relegated to the background and overlooked when frontline workers are heralded. Community pharmacists are the most accessible healthcare practitioners, which is further proven during the pandemic as they continued to provide direct patient care despite restrictions imposed by the government due to the pandemic. Due to the inaccessibility of other healthcare practitioners during this time, community pharmacists have reduced the burden on the healthcare system by diverting the influx of patients away from hospitals through triaging and screening patients. Community pharmacists have played various roles in supporting the healthcare system during COVID-19: delivering medications to patients, educating patients on telehealth services, assessing patients for renewal of chronic medications, performing consultations on minor ailments, clarifying misconceptions about COVID-19 treatments, and contributing to COVID-19 screening. Alongside ICU nurses, physicians, and respiratory therapists, hospital pharmacists have been part of the COVID-19 efforts and their roles include management of drug shortages, development of treatment protocols, participation of patient rounds, interpretation of lab results for COVID-19, participant recruitment for clinical trials, exploration of new drugs, medication management advice, and antimicrobial stewardship. Further support from pharmacists will be needed once a vaccine is launched in order to reach population-wide coverage. Amid COVID-19, pharmacists have not stopped working as frontline workers and they should be recognized as such.